2001
DOI: 10.1097/00001756-200110290-00032
|View full text |Cite
|
Sign up to set email alerts
|

Brain prolyl oligopeptidase activity is associated with neuronal damage rather than β-amyloid accumulation

Abstract: Prolyl oligopeptidase (POP) have been suggested to participate in the pathogenesis of Alzheimer's disease (AD). In this study the activity of POP is evaluated in AD patients and in transgenic mice with substantial deposits of beta-amyloid (Abeta). In AD cases, the POP activity displayed a significant negative correlation with the scores of senile/neuritic plaques and neurofibrillary tangles but not with Abeta-load. The transgenic mice with high levels of Abeta did not have altered POP activity compared to wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Of course, based on these observations, it is not possible to state whether the increased PEP expression by individual neurons contributes to AD pathology. However, the neuroprotective effects of PEP inhibition on one side and the frequent co-occurance of robust PEP expression and morphological characeristics of neurodegeneration in the AD brain on the other side indicate that increased PEP expression may play a role in ADassociated neurodengeration as also suggested in by Laitinen et al (20). The brains of AD patients are also characterized by a robust activation of microglial cells and astrocytes in proximity to b-amyloid plaques.…”
Section: Pep Expression In Human Brainmentioning
confidence: 77%
“…Of course, based on these observations, it is not possible to state whether the increased PEP expression by individual neurons contributes to AD pathology. However, the neuroprotective effects of PEP inhibition on one side and the frequent co-occurance of robust PEP expression and morphological characeristics of neurodegeneration in the AD brain on the other side indicate that increased PEP expression may play a role in ADassociated neurodengeration as also suggested in by Laitinen et al (20). The brains of AD patients are also characterized by a robust activation of microglial cells and astrocytes in proximity to b-amyloid plaques.…”
Section: Pep Expression In Human Brainmentioning
confidence: 77%
“…Since many of these neuropeptides are connected with learning and memory functions [11,12], and also with neurodegenerative disorders such as Parkinson’s and Alzheimer’s diseases [11], POP has been considered as a target for treatment of different neuropsychiatric and cognitive disorders [13,14]. It has been suggested that POP plays a role in aging processes since its activity has been reported to be associated with neuronal degeneration [15,16]. In addition, alterations in enzymatic activities of plasma POP have been measured in many different psychiatric conditions [17,18] and in Parkinson’s and Alzheimer’s diseases [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed to act both extracellularly, where it is involved in the maturation and degradation of peptide hormones and neuropeptides, including substance P and neurotensin (Bellemere et al, 2004;Cunningham and O'Connor, 1997), and intracellularly where it may be part of signaling pathways or contribute to transport and secretion of proteins and peptides including Alzheimer amyloid beta (Ab) protein Schulz et al, 2002Schulz et al, , 2005. It has been speculated that PEP may play a role in the pathogenesis of AD based on studies showing abnormal expression of this enzyme in brain samples from AD patients and in transgenic mice overexpressing Alzheimer amyloid precursor protein (APP) (Cunningham and O'Connor, 1997;Laitinen et al, 2001;Rossner et al, 2005). PEP inhibitors have also been shown to have neuroprotective and memory-enhancing effects that have been attributed to their ability to modify neuropeptide metabolism (Cunningham and O'Connor, 1997;Makinen et al, 1994).…”
mentioning
confidence: 99%